Comparative pharmacokinetics and pharmacodynamics of a PEGylated recombinant human growth hormone and daily recombinant human growth hormone in growth hormone-deficient children - Hou L; Chen ZH; Liu D; Cheng YG; Luo XP (Dove Medical Press, 2015)
Ling Hou,1,* Zhi-hang Chen,2,* Dong Liu,3 Yuan-guo Cheng,2 Xiao-ping Luo1 1Department of Pediatrics, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 2Department of Pharmacy, Beijing Institute of Microbiology and Epidemiology, Beijing, 3Department of Pharmacy, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China *These authors contributed equally to this study Objective: Recombinant human growth hormone (rhGH) replacement therapy in children generally requires daily subcutaneous (sc) injections, which may be inconvenient for patients. Jintrolong® is a PEGylated rhGH with the purpose of weekly sc injections. The aim of the current study was to examine the pharmacokinetics, pharmacodynamics, safety, and tolerability of multiple sc doses of Jintrolong® vs daily doses of rhGH. Design and methods: Twelve children with growth hormone deficiency participated in this single-center, open-label, crossover Phase I trial. All subjects received daily sc injections of rhGH at 0.0286 mg/kg/d for 7 days, followed by a 4-week washout period and six weekly doses of Jintrolong® at 0.2 mg/kg/w. Results: In comparison with rhGH, sc injection of Jintrolong® produced a noticeably higher Cmax, significantly longer half-life (t1/2), and slower plasma clearance, signifying a profile suitable for long-term treatment. The ratio of the area under the concentration vs time curve (AUC) after the seventh and first injections (AUC(0–∞)7th/AUC(0–∞)1st) of rhGH was 1.02, while the AUC(0–∞)6th/AUC(0–∞)1st of Jintrolong® was 1.03, indicating no accumulation of circulating growth hormone. There was no significant difference in the change in insulin-like growth factor-1 expression produced by 7 days of sc rhGH and weekly Jintrolong® injections. There were no severe adverse events during the trial. Conclusion: The elimination rate of Jintrolong® was slower than that of sc rhGH. No progressive serum accumulation of Jintrolong® was found. The changes in insulin-like growth factor-1 expression produced by rhGH and Jintrolong® were comparable, indicating similar pharmacodynamics. Our results demonstrate that Jintrolong® is suitable for long-term growth hormone treatment in children with growth hormone deficiency. Keywords: long-acting growth hormone, phase I, multiple-dose